Migrant elders in Hainan, China, report better health and lower depression than local-born elderly residents - Wei Wang; Qingxia Wu; Xiaoyang Yang; Xin He; Xuefang An (Taylor & Francis Group, 2017)
Background: The number of migrant elders is increasing due to ageing of the global population and increasing life expectancy. There is accumulating evidence of the impact of internal or international migration on health. Aim: To compare the health and depression of local and migrant elders in Hainan province. Subjects and methods: Health and depression were assessed by the Self-Rated Health Measurement Scale Version 1.0 (SRHMS V1.0) and the Geriatric Depression Scale (GDS), respectively. The relationship between health and depression was investigated, along with the three sub-scales of SRHMS and the potential independent variables. Results: In total, 564 valid questionnaires were returned. Migrant elders were younger, had higher education levels and monthly income, and lower prevalence rates of chronic diseases than the local elders. The SRHMS scores were significantly higher, while the GDS scores were statistically lower in the migrant elders than the locals. Depression was negatively correlated with health (r = -0.674, p = 0.0000). Moreover, the three sub-scales of SRHMS were correlated with age, birth place, marital status, chronic diseases, GDS and/or educational level. Conclusion: Migrant elders self-reported better health and lower depression compared to the local elders. Differences in age, education, monthly income and chronic diseases might be influencing factors.